PENINGKATAN PEMAHAMAN SISWA TERHADAP KONSEP-KONSEP MATEMATIKA MELALUI PETA KONSEP - Pitadjeng, Pitadjeng (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
Abstract Observations reveal that a lot of elementary school pupils have difficulties in understanding mathematics concept. The problem is how we can improve the effectiveness of mathematics concept map. The aims of this study is to develop mathematical instruction using a concept map to improve the pupils’s achievement. This is a classroom action research in the fifth grade. The data were collected by means of a test, observation, questionnaire and field note. The source of the data were the fifth garde students of the Elementary School of Sekaran 02, at Gunung Pati Semarang. The results indicate that the use of concept map can improve the pupils’ understanding of mathematical concepts. The responses reveal that the instruction using or constructing a concept map makes the mathematics learning easier and interesting so that the instruction can make the pupils like the mathematic lesson. Keywords: concept mapping, mathematics learning